In overweight or obese adults, does increased daily fiber intake result in more weight reduction compared to routine fiber intake?. Issue 12 (December 2017) - Patel, Miral; Miller, Deborah
Abstract : EVIDENCE‐BASED ANSWER : Probably not. A bean‐based high fiber is not superior to a low‐carbohydrate diet for weight loss (SOR: C, conflicting RCTs). Fiber goals may be easier to reach with a beanbased diet than a fruit, vegetable, and grain‐based diet (SOR: C, small RCT).